2018
DOI: 10.1136/bjophthalmol-2018-312781
|View full text |Cite
|
Sign up to set email alerts
|

Unmeasurable small size superficial and deep foveal avascular zone in nanophthalmos: the Collaborative Nanophthalmos OCTA Study

Abstract: AimTo study the macular structure and vasculature in consecutive nanophthalmic eyes using optical coherence tomography angiography.MethodsThis is a prospective, multicentre, cross-sectional study of patients with nanophthalmos (one or both eyes). The superficial and deep foveal avascular zones (FAZ) were measured both manually and with the machine’s built-in automated measurement tool. Correlations between best corrected visual acuity (BCVA), central macular thickness (CMT) and subfoveolar choroidal thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…During a mean follow-up duration of 65.3 months, the final BCVA improved or stabilized in 89.6% of eyes; however, OCT/OCTA imaging revealed that the extent of improvement was limited by photoreceptor and pigment epithelial damage resulting from macular dysplasia or chronic retinal detachment. The OCTA role in defining macular status and visual potential is consistent with Mansour's ( 23 ) findings in nanophthalmos. In addition, in our nanophthalmos group, secondary glaucoma combined with optic atrophy was also the main reason for poor final vision.…”
Section: Discussionsupporting
confidence: 84%
“…During a mean follow-up duration of 65.3 months, the final BCVA improved or stabilized in 89.6% of eyes; however, OCT/OCTA imaging revealed that the extent of improvement was limited by photoreceptor and pigment epithelial damage resulting from macular dysplasia or chronic retinal detachment. The OCTA role in defining macular status and visual potential is consistent with Mansour's ( 23 ) findings in nanophthalmos. In addition, in our nanophthalmos group, secondary glaucoma combined with optic atrophy was also the main reason for poor final vision.…”
Section: Discussionsupporting
confidence: 84%
“…This suggests that light-induced CCT changes may affect scleral growth, and then, AL. However, further studies are required to validate this suggestion, considering the lack of pathohistological evidence collated over time [22]. Moreover, gene-environment interactions may also play a role in AL elongation and myopia development [23].…”
Section: Plos Onementioning
confidence: 99%
“…Special anatomic features of nanophthalmos. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] zonular dialysis occurred after a cotton applicator was applied to the injection site in an effort to control the reflux of hyaluronic acid or air. The lens dislocated into the vitreous cavity in Cases 4 and 5 after the eye was reinflated with a balanced salt solution injected through a limbal incision.…”
Section: Resultsmentioning
confidence: 99%
“…These eyes have very anterior insertion of the retina, a large lens, short zonules, a shallow anterior chamber (AC) (with a propensity for angle closure), and a noticeably thickened sclera and choroid (Figure 1). [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Vitrectomy is dangerous because it can result in peripheral holes (anterior retinal insertion), 12 which can cause an exudative RD to become more complex and require silicone oil tamponade or multiple surgical procedures. 12,13 In this case series, we describe the anatomic and visual results of surgical procedures for serous RD with retina-lens touch in eyes with nanophthalmos.…”
Section: Introductionmentioning
confidence: 99%